Produção de material didático para a leitura e escrita do gênero narrativa sob a perspectiva da Escola de Sydney - Della Mea, Tatiana (2021)
This research has as objective the elaboration of a textbook on literary narratives for a 7th grade class of an elementary school, following the Genre Pedagogy precepts of the Sydney School (MARTIN; ROSE, 2008; ROSE; MARTIN, 2012) in order to develop reading and writing skills, which can promote a better performance in the students' level of literacy, as well as providing other Portuguese language teachers with a different methodology from those presented in Portuguese language textbooks, assisting them in their classes. For the elaboration of the activities in the textbook, we used the narrative “Uma história de assombração” (CAPARELLI; BRAGANÇA, 2015) as a based-text, and the activities were built based on the guidelines provided by the Pedagogy based on Text Genres, evidencing the strategies for reading and writing established by the Teaching and Learning Cycle proposed by the Australian school, focusing on the third phase of the project called Reading to Learn: Reading Preparation (Deconstruction), Joint Construction and Independent Construction. Furthermore, regarding the linguistic analysis, the textbook questions are related to the three language metafunctions - ideational, interpersonal and textual - according to the Systemic-Functional Linguistics (HALLIDAY; MATTHIESSEN, 2014) perspective. Thus, the textbook is divided into three parts that correspond to the stages of the Teaching and Learning Cycle: 1) Reading preparation (Deconstruction); (2) Joint Construction; and (3) Independent Construction. In each part, we present an Activity Plan composed of the identification data of the school, the class and the period of application of the activities corresponding to each stage. We also highlight the theme of the class, the steps to be followed for the development of activities, the methodology, the resources used and the evaluation of the students' performance in the proposed tasks. As activities are being presented in the Plan (ROSE, 2015), we include and highlight several items called “Instructions for Teachers”, in order to provide teachers with guidelines for the tasks application. Considering the textbook presented here, our intention is to provide subsidies for a productive work in the classroom and also to motivate the development of new proposals for teaching reading and writing of a narrative genre according to the strategies of the Teaching and Learning Cycle.